A protocol using compact 3D printed micro-optical elements for protein identification from low-intensity amino-acid Raman signals - Weinacker, Jannis; Bhandari, Bikash Kumar; Viejo Rodriguez, Alba; West, Charlotte; De Angelis, Francesco; Tantussi, Francesco; Maccaferri, Nicolò; Goldman, Nick; Wegener, Martin (Advanced Materials Technologies, 2025)
When performing optical high-speed single-molecule spectroscopy and identification, low signal intensities pose a challenge. Fortunately, for many applications, the number of possible molecules in the specimen is small or limited. For such cases, a protocol is presented that uses only a small number of very sensitive hence expensive detectors. The protocol starts with optimizing spectral regions, one per detector, so that different molecules become best distinguishable. Experimentally, the spectral regions are extracted from the continuous spectrum using a custom-made micro-optical element. In the ray-optics picture, it guides all rays in a spectral region onto the entrance of an optical fiber connected to one detector. The shape of the micro-optical element is derived by applying Snell's law to the given geometrical boundary conditions. A proof-of-concept measurement using a dedicated demonstrator refractive optical element in combination with a continuous white-light source is performed. Indeed, the element selects the correct spectral regions and couples the light into the correct fibers. For the example of the identification of single amino acids in a protein, the protocol leads to a higher correct identification rate. Therefore, this protocol is useful for such protein identification experiments as performed in the EU project ProID.
Gesehen am 18.08.2025